2020
DOI: 10.1186/s12974-020-01854-w
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammatory mechanisms of post-traumatic epilepsy

Abstract: Background: Traumatic brain injury (TBI) occurs in as many as 64-74 million people worldwide each year and often results in one or more post-traumatic syndromes, including depression, cognitive, emotional, and behavioral deficits. TBI can also increase seizure susceptibility, as well as increase the incidence of epilepsy, a phenomenon known as post-traumatic epilepsy (PTE). Injury type and severity appear to partially predict PTE susceptibility. However, a complete mechanistic understanding of risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 153 publications
0
46
0
Order By: Relevance
“…The general prognosis of epilepsy is favorable for the majority of patients and 55-68% of them tend to achieve long-term remission [23], but in the case of generalized tonic-clonic seizures, nocturnal seizures and refractory or drug-resistant epilepsy, death is not uncommon [24]. The development of epilepsy can be associated with a wide variety of factors, including genetic predisposition, malformations, traumatic brain injuries that occur annually in 64-74 million people [25], chemical exposure, hypoxia or stroke. Many of these pathologies are associated with neuronal death.…”
Section: Epilepsy the Characteristics Of The Pathogenesis The Relationship With Inflammatory Processes Drug-resistant Epilepsymentioning
confidence: 99%
See 3 more Smart Citations
“…The general prognosis of epilepsy is favorable for the majority of patients and 55-68% of them tend to achieve long-term remission [23], but in the case of generalized tonic-clonic seizures, nocturnal seizures and refractory or drug-resistant epilepsy, death is not uncommon [24]. The development of epilepsy can be associated with a wide variety of factors, including genetic predisposition, malformations, traumatic brain injuries that occur annually in 64-74 million people [25], chemical exposure, hypoxia or stroke. Many of these pathologies are associated with neuronal death.…”
Section: Epilepsy the Characteristics Of The Pathogenesis The Relationship With Inflammatory Processes Drug-resistant Epilepsymentioning
confidence: 99%
“…Several researchers have shown that the concentration of IL-4, IL-8 and IL-17 can correlate with the frequency and severity of seizures, suggesting a key role for cytokines in the diagnosis and treatment of epilepsy [38,40]. Most chemokines and their receptors promote neuroinflammation by involving peripheral monocytes and promoting glial cell activation [25]. Table 1 provides examples of some mediators involved in neuroinflammation and epilepsy and their role in these processes.…”
Section: Epilepsy the Characteristics Of The Pathogenesis The Relationship With Inflammatory Processes Drug-resistant Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to cellular mediators, specific inflammatory cytokines and chemokines have been demonstrated to be pro-epileptogenic [ 17 ]. These include IL1β, IL6, TNFα, TGFβ, [ 6 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%